PERAN ORGANISASI SANTRI KREATIF AL HIKMAH (OSKA) DALAM MENINGKATKAN KEDISIPLINAN SANTRI DI PONDOK PESANTREN AL HIKMAH MUHAMMADIYAH SUKOHARJO TAHUN AJARAN 2022/2023 - Azizah, Annisa Nur; Nashir, Muhammad Jafar; Rochmawan, Alfian Eko (MAMBA'UL 'ULUM, 2024)
This research aims to determine the role of the Al Hikmah Creative Santri Organization (OSKA) in improving student discipline and aims to determine the supporting and inhibiting factors of the Al Hikmah Creative Santri Organization (OSKA) in improving student discipline at the Al Hikmah Muhammadiyah Sukoharjo Islamic Boarding School. The type of research method uses qualitative methods. Based on research in the field, it shows that the role of the Al Hikmah Creative Santri Organization (OSKA) in improving student discipline: (1) by providing a good example, giving direction, giving punishment, conducting supervision and finally evaluating with students and ustadzah. (2) Supporting factors for the Al Hikmah Creative Santri Organization (OSKA) in improving student discipline at the Al Hikmah Muhammadiyah Sukoharjo Islamic Boarding School are the attention of the supervising ustadzah and adequate infrastructure. While the inhibiting factors are the influence of close friends ('ashabiyah), lack of awareness of students and lack of cooperation between OSKA administrators.